2012
DOI: 10.1124/jpet.112.193433
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein Is a Major Determinant of Norbuprenorphine Brain Exposure and Antinociception

Abstract: Norbuprenorphine is a major metabolite of buprenorphine and potent agonist of , ␦, and opioid receptors. Compared with buprenorphine, norbuprenorphine causes minimal antinociception but greater respiratory depression. It is unknown whether the limited antinociception is caused by low efficacy or limited brain exposure. Norbuprenorphine is an in vitro substrate of the efflux transporter P-glycoprotein (Mdr1), but the role of P-glycoprotein in norbuprenorphine transport in vivo is unknown. This investigation tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 47 publications
1
46
0
Order By: Relevance
“…In vitro studies appear in agreement that buprenorphine is most likely not a P-gp substrate (111,166,167), while nobuprenorphine is (36,166). The apparent P-gp mediated efflux of norbuprenorphine at the BBB may explain its minimal antinociceptive effects, despite its opioid receptor affinities.…”
Section: Buprenorphinementioning
confidence: 83%
See 2 more Smart Citations
“…In vitro studies appear in agreement that buprenorphine is most likely not a P-gp substrate (111,166,167), while nobuprenorphine is (36,166). The apparent P-gp mediated efflux of norbuprenorphine at the BBB may explain its minimal antinociceptive effects, despite its opioid receptor affinities.…”
Section: Buprenorphinementioning
confidence: 83%
“…Another P-gp knock-out mice study demonstrated that the brain/plasma ratio of norbuprenorphine was significantly greater, as was the magnitude and duration of its antinociceptive effects, relative to wild-types. These results suggest that P-gp plays a major role in limiting the BBB access of norbuprenorphine, potentially explaining its minimal antinociceptive effects (166). Administration of the P-gp inhibitor PSC833 in mice was found to significantly increase the respiratory depressive effects of buprenorphine and norbuprenorphine, as well as significantly increase plasma concentrations and reduce brain efflux of norbuprenorphine.…”
Section: Buprenorphinementioning
confidence: 96%
See 1 more Smart Citation
“…After these reports, for various compounds, their brain distribution across the BBB has been compared using the Mdr1a knockout or Mdr1a/1b double knockout mouse. These compounds included the following: fluorescent dye rhodamine-123 (de Lange et al 1998); anti-cancer agents such as vinblastine (van Asperen et al 1999); the cardiovascular agent, digoxin (Kawahara et al 1999); the immunosuppressant, cyclosporin A (Kwei et al 1999); the corticosteroid, dexamethasone (Meijer et al 1998); the glucocorticoid, prednisolone (Karssen et al 2002); the antifungal agent, itraconazole (Miyama et al 1998); anti-HIV1 protease inhibitors (Kim et al 1998); opioid analgesics (Chen and Pollack 1998;Dagenais et al 2002); neurokinin-1 receptor antagonists (Smith et al 2001); and anticonvulsants such as, enaminone (Cox et al 2001) and norbuprenorphine (Brown et al 2012). Interestingly, it has been revealed that adverse effects or pharmacodynamic effects of various molecules in the brain are also related to the function of P-gp (Muller et al 2003;Tahara et al 2005;Morimoto et al 2008).…”
Section: The Role Of Drug Transporters In Cns Transportmentioning
confidence: 97%
“…Buprenorphine and also the active metabolite norbuprenorphine were assayed by LC-MS-MS (Liquid Chromatography Tandem Mass Spectrometry, Simbec Research Ltd., Merthyr Tydfil, UK), since animal studies identify norbuprenorphine as a potent respiratory depressant [18,19,20,21]. …”
Section: Methodsmentioning
confidence: 99%